Genetic phylogeography and maternal lineages of 18 Chinese black goat breeds - Tao Zhong; Qian-Jun Zhao; Li Li Niu; Jie Wang; Peng Fei Jin; Wei Zhao; Lin Jie Wang; Li Li; Hong Ping Zhang; Yue-Hui Ma (Springer, 2013)
To understand the origin and genetic phylogeography of Chinese black goats, variations of mitochondrial DNA were characterised with 394 goats from 18 breeds, including 91 new individuals from regions poorly studied until now. Comparison of a 481-bp segment revealed a total of 192 haplotypes with 141 variable sites. The haplotype and nucleotide diversities ranged from 0.782 ± 0.079 to 1.000 ± 0.020 and from 0.009 ± 0.001 to 0.045 ± 0.006, respectively, indicating a relatively high genetic diversity in Chinese black goats. Phylogenetic analyses identified five haplogroups (A, B1, B2, C and D). The dominant haplogroups A, B1 and B2 were distributed in most of breeds, while the haplogroups C and D were only presented in the breeds located in north or northwest of China. Analysis of molecular variance and multidimensional scaling plot of F ST analyses indicated no obvious geographic structure among breeds. Furthermore, the migration rates revealed that a wide range of gene flow or gene exchange occurred among breeds, which may result in the weak geographic structure of Chinese black goats. Population expansion analysis based on mismatch distribution indicated that two expansion events in Chinese black goats occurred at 10 and 28 mutational time units. Finally, our findings indicate the multiple maternal origins of Chinese black goats and more gene flow (female-mediated) which occurred during their domestic and breeding histories.